Porcine choroid plexus-Riems cell line demonstrates altered polarization of transport proteins compared with the native epithelium - Hochstetler, Alexandra; Hulme, Louise; Delpire, Eric; Schwerk, Christian; Schroten, Horst; Preston, Daniel; Simpson, Stefanie; Blazer-Yost, Bonnie L. (American journal of physiology. Cell physiology, 2022)
The choroid plexus epithelium (CPe) forms a barrier between the cerebral blood supply and the cerebrospinal fluid (CSF), establishing the blood-CSF barrier (BCSFB). CSF is actively secreted by the CPe via tightly controlled processes involving multiple channels, transporters, and pumps. The importance of controlling CSF production and composition has been accentuated recently with an appreciation of CSF dysfunction in many pathologies. For mechanistic studies of CSF production, isolated CPe cell lines are valuable for the testing of hypotheses and potential drug targets. Although several continuous CPe cell lines have been described, none appear to have all the characteristics of the native epithelium and each must be used judiciously. The porcine choroid plexus-Riems (PCP-R) cell line forms a high-resistance monolayer characteristic of a barrier epithelium. Conservation of this phenotype is unusual among CPe cell lines, making this model useful for studies of the effects of infection, injury, and drugs on permeability. We have recently discovered that, although this line expresses many of the transporters expressed in the native tissue, some are mispolarized. As a result, inferences regarding fluid/electrolyte flux and the resultant CSF production should be pursued with caution. Furthermore, extended culture periods and changes in media composition result in significant morphological and functional variability. These studies provide a more detailed characterization of the PCP-R cell line concerning transporter expression, polarization, and functionality, as well as plasticity in culture, with the goal to provide the scientific community with information necessary to optimize future experiments with this model.